Estratégias de operações em recicladoras de resíduos eletroeletrônicos - Moraes, Daniela da Gama e Silva Volpe Moreira de (Universidade Federal de São Carlos, 2019)
Operations management can play a decisive role in the development of competitive positions for companies. Many works refer to operations management as the area responsible for reducing companies’ environmental impact through, for example, materials reuse, increasing energy efficiency, reducing waste generation, waste disposal etc. However, the literature highlights the lack of alignment between environmental issues and operations strategies. In Brazil, the National Solid Waste Policy, instituted by Law nº 12305/2010 and regulated by Decree nº 7404/2010 imposes the principle of shared responsibility for the product life cycle and the reverse logistics system as a socioeconomical instrument. According to this regulation, manufacturers, importers, distributors, and traders of electronic products and their components are required to structure and implement reverse logistics systems. This fact promotes the organization of new markets, leads to the need for an adequate e-waste management and a better understanding of the practices adopted by companies that recycle e-waste. In research conducted in Web of Science and Scopus databases until August 2018 no articles that analyzed the operations strategies in e-waste recyclers were found, confirming the opportunity to develop the theory of operations strategy in this sector. Due to the necessity to find solutions to e-waste management in the Brazilian municipalities and that these solutions could be more easily and effectively implemented if integrated into operations strategies, in this thesis we aim to identify and analyze the operations strategies of companies that recycle e-waste and investigate how these strategies incorporate environmental sustainability actions. We adopted a qualitative approach, based on the conduction of five case studies. Even with different business models adopted, the results point out that environment is considered a key competitive priority for the companies analyzed, although quality stands out among the competitive priorities adopted. It was also verified that the adoption of environment as a competitive priority also affected the decision areas, especially the infrastructural one. In addition, it was verified that environmental issue is considered strategic and acts as a facilitator for the adoption of environmental practices. All companies researched adopt pollution prevention programs and waste reduction. However, it should also be noted the implementation of the following environmental practices: reduction of energy consumption, ISO 14001, corporate social responsibility and environmental planning and control, which were adopted by 4 of 5 companies investigated. From the theoretical point of view, the study points out that environment must be incorporated as a competitive priority, confirming the expansion of the traditional competitive priorities.
Operations strategies in e-waste recycling plants
Keywords: Estratégia de operações; Resíduos eletroeletrônicos; Prioridades competitivas; Questões ambientais; Operations strategy; E-waste; Competitive priorities; Environmental issues; ENGENHARIAS::ENGENHARIA DE PRODUCAO